Silent changes in taxonomic, functional and phylogenetic diversity of birds in Qiyunshan National Nature Reserve, south China - Binqiang Li; Jian Lu; Xin Zhong; Daohan Li; Bailin Li; Nehafta Bibi; Kechuan Linghu; Shanjun Ma; Pinghua Zhong (Biodiversity Data Journal)
Temporal taxonomic shifts have been documented in bird communities within protected areas. However, the potential impact of these changes on functional diversity and phylogenetic diversity remains poorly understood. In this study, we monitored bird communities in Qiyunshan National Nature Reserve in southern China for nine years (2014-2022). We examined temporal trends in taxonomic, functional and phylogenetic diversity metrics and compared observed phylogenetic diversity values with expected values to determine the mechanisms driving community assembly. Additionally, we evaluated the temporal trend of beta diversity. A total of 118 bird species were recorded, with the dominant species including Chestnut Bulbul (Hemixos castanonotus), Grey-cheeked Fulvetta (Alcippe morrisonia) and Great Tit (Parus major). We found that species turnover was the principal driver of temporal variations in species composition. However, species richness, functional diversity and phylogenetic diversity fluctuated throughout the study period, showing no clear trend of increase or decrease. Our findings indicate that the composition of bird communities is shaped by environmental filtering and neutral processes. The changes in taxonomics may be due to changes in the availability of resources and random substitution arising from the dispersion process. Protected areas have the potential to attract new bird species with similar functional and genetic relationships to those already present. This leads to minimal changes to overall functional and phylogenetic diversity, suggesting a degree of functional redundancy amongst species that are replaced or added. Notably, we observed a persistent increase in species loss over time, raising concerns about the potential impact on the future functional stability of the system. We highlight that the asynchronous patterns of taxonomic, functional and phylogenetic diversity in birds emphasise the importance of multidimensional diversity metrics. Consequently, we suggest that functional and phylogenetic diversity should be regarded as essential indicators alongside species richness when evaluating conservation outcomes in nature reserves. This approach provides a more comprehensive understanding of the complexity of ecological communities and provides information for more effective conservation strategies.